Edible films gelatin-based obtained from mahi-mahi skin (Coryphaena hippurus) and oregano extract: Physicochemical, antimicrobial, structural and surface characteristics (Scientia Agropecuaria, 2021)
Edible films were elaborated from gelatin solutions (4% w/v) of mahi-mahi skin (Coryphaena hippurus) with 2,5; 5; 7,5 and 10% v/v of oregano extract (OE) and its physicochemical, antimicrobial, structural and surface properties were determined. The control and with 2.5% OE films showed the lowest moisture and opacity values ​​and the highest viscosity values. All films with OE inhibited the growth of Staphylococcus aureus and Proteus vulgaris. Alone films with 10% OE showed antimicrobial activity against all the strains evaluated. Scanning electron microscopy showed that the incorporation of oregano extract in the film-forming solutions, FFS, was related to an increase in the presence of oil droplets in the films, showing the lipid fraction of OE. Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM) analyzes showed the interaction between gelatin, plasticizer, and oregano extract in all films. In conclusion, this study demonstrated the viability of mahi-mahi skin gelatin edible films with OE incorporated for their application as packaging with antimicrobial action in foods susceptible to spoilage by microorganisms.
Keywords: Edible film; biomaterial; oregano extract; fish waste